PENGEMBANGAN PRAKTIKUM VIRTUAL URINALISIS SEBAGAI MEDIA PEMBELAJARAN BIOLOGI SISWA SMA KELAS XI - Ade Suryanda; Rusdi Rusdi; Dewi Kusumawati (Universitas Negeri Jakarta, 2017)
Lab work has become one of the most important activities in learning Biology. Urinalysis requires special treatment because urinalysis using urine as a sample to be analyzed. There have been limitations in implementation of the lab work of urinalysis at high school level. Learning media such as virtual lab work of urinalysis was expected to overcome the limitations. The aim of this research was to develop virtual lab work as learning media of Biology. The research was held at Senior High School 4 Tangerang, using research and development method. Research and information collecting, planning, product development, and try-out and revision were the steps in this research. Instrumen used were questionnaires for need assessment for students, interviews guide for Biology teacher, and questionnaires of feasibility for media expert, material expert, Biology teacher, and students. In the try-out and revision steps, media expert and material expert were involved in feasibility testing, meanwhile Biology teacher and students grade XI at Senior High School 4 Tangerang were involved in field testing. The average percentage of all test products scored 81,76%. The result of this research showed that the virtual lab work of urinalysis could be utilized as one of learning media of Biology for Senior High School grade XI.